The association between naturalistic use of psychedelics and co-occurring substance use disorders - Rabinowitz, Jonina; Lev-Ran, Shaul; Gross, Raz (Frontiers in Psychiatry, 2023)
Objective Classic psychedelics (LSD, psilocybin, and peyote/mescaline) have been used to support addiction treatment in a variety of contexts ranging from ceremonial use to clinical trials. The aim of this study was to test the hypothesis that past naturalistic use of classic psychedelics would be associated with decreased prevalence of substance use disorder, when controlling for known confounders. Methods This cross-sectional study used 2017 NSDUH survey data to evaluate the association between past use of the classic psychedelics LSD, psilocybin and peyote/mescaline and past year substance dependence or abuse. We calculated adjusted odds ratios by multivariate logistic regression, controlling for a range of sociodemographic variables, use of non-psychedelic illicit drugs and mental health related variables. Results A total of 56,276 participants were included in this study. Past use of LSD and psilocybin were associated with increased odds of substance dependence or abuse compared to those who had never used psychedelics before, and this was more likely for those who had used LSD more recently. However, prior use of peyote or mescaline was associated with lower odds of past year substance dependence or abuse compared to people who had never used psychedelics before (aOR = 0.68, p < 0.001). Past use of classic psychedelics was not associated with nicotine dependence. Conclusion Past use of peyote/mescaline was associated with decreased odds of substance use disorder compared to people who had never used psychedelics before, while past use of LSD or psilocybin was not. It remains unclear whether this difference is due to pharmacological differences between these compounds or simply due to the context in which peyote/mescaline are traditionally taken. Future research should investigate why naturalistic use of different psychedelics is associated with different substance use disorder effects.